Selective, Anisotropic, or Consistent Polarized‐Photon Out‐Coupling of 2D Organic Microcrystals. Issue 33 (7th July 2022) - Li, Zhong‐Qiu; Ma, Dian‐Xue; Xu, Fa‐Feng; Dan, Ti‐Xiong; Gong, Zhong‐Liang; Shao, Jiang‐Yang; Zhao, Yong Sheng; Yao, Jiannian; Zhong, Yu‐Wu
Abstract: Nano‐ and micromaterials with anisotropic photoluminescence and photon transport have widespread application prospects in quantum optics, optoelectronics, and displays. But the nature of the polarization information of the out‐coupled light, with respect to that of the source luminescence, has never been explored in active optical‐waveguiding organic crystals. Herein, three different modes (selective, anisotropic, and consistent) of polarized‐photon out‐coupling are proposed and successfully implemented in a set of 2D organic microcrystals with highly linearly‐polarized luminescence. It is found that the polarization direction and degree of the luminescence out‐coupled through different waveguiding channels can either be essentially retained or distinctly changed with respect to those of the original luminescence, depending on the molecular arrangement and the orientation of transition dipole moments of the crystal. This work demonstrates the promising potential of 2D emissive microcrystals in multi‐channel polarized photon transport. Abstract : Multichannel selective, anisotropic, or consistent polarized‐photon out‐coupling has been realized in a set of 2D organic microcrystals, with the polarization direction and degree being either varied or retained with respect to the source luminescence. The molecular arrangement and spatial distribution of the transition dipole moments are found to play prominent roles in determining the polarization properties of the source and out‐coupled emissions.